Formulation and Evaluation of Lipid/Soluplus-Stabilized Nanocrystals of Paclitaxel and Bosutinib for a Synergistic Effect in Non-Small Cell Lung Cancer Therapy - Kumar M.; Goswami P.; Jha A.; Dhapte-Pawar V.; Koch B.; Mishra B. (My University, 2025)
Tyrosine kinase inhibitors have been employed for the treatment of lung cancer, owing to their role in regulating irregulated pathways or mutated genes. Bosutinib, a nonreceptor tyrosine kinase, has been recently investigated for lung cancer treatment. Bosutinib can also be used with paclitaxel as a combinatorial approach to receive a synergistic effect for the effective management of lung cancer. Furthermore, the nanocrystals of each can also be prepared and in combination can produce a more pronounced impact than the drug combination. Herein, the prepared Soluplus/lipid-stabilized nanocrystals of paclitaxel and bosutinib were rod to cubic in shape of about 150-250 nm. The nanocrystals were stable, provided controlled drug release, and exhibited a higher aerosolization performance. The nanocrystal combination demonstrated higher anticancer activity than the drug combination synergy against A549 cancer cells. The nanocrystals increased the level of cellular internalization in cancer cells, thereby inducing higher ROS generation and apoptosis of cancer cells. Furthermore, the lipid/Soluplus-stabilized nanocrystals exhibited higher translocation potential compared with only Soluplus-stabilized nanocrystals. The nanocrystals administered intratracheally showed a lower drug distribution to other organs, with prolonged drug retention in the lungs, suggesting the higher efficacy of developed nanocrystals in targeting the lungs. In conclusion, lipid-modified nanocrystals can be a novel approach for the effective management of lung cancer. © 2025 American Chemical Society.